IMPLEMENTASI IOT BERBASIS ESP32 UNTUK PEMANTAUAN KUALITAS UDARA DI ALUN-ALUN BUNG KARNO UNGARAN - Muhammad Afrizal Darmawansyah; Priyadi; Daniel Rudjiono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Real-time air quality monitoring is essential for providing timely and continuous environmental information. This study aims to design, implement, and evaluate an Internet of Things (IoT)-based air quality monitoring system using an ESP32 microcontroller. The system utilizes an MQ-135 sensor to detect carbon dioxide (CO₂) concentration and a DHT11 sensor to measure air temperature and humidity. The measured data are displayed on a 16×2 LCD and transmitted via a Telegram Bot to support remote monitoring. This research employed the Research and Development (R&D) method using the Prototype model. The system testing results showed that the developed system was capable of detecting CO₂ concentrations ranging from 194 to 2045 ppm, temperatures from 14 to 39.9°C, and humidity levels from 53% to 95% RH. All system components, including the sensors, LCD, indicator lights, and Telegram Bot, functioned according to the design specifications, achieving a 100% success rate during testing. Field testing at Alun-alun Bung Karno Ungaran demonstrated that the system was able to acquire, process, and transmit environmental data in real time with stable operation. The implementation results indicate that the developed system provides fast, integrated, and easily accessible air quality information, making it suitable as an IoT-based air quality monitoring prototype.